On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov. - Vinokurov, Nikolay N.; Kment, Petr (Zootaxa, 2021)
In this paper, we present new data on the genus Macrosaldula Leston & Southwood, 1964 based on material held in the collections of the National Museum (Prague, Czech Republic) and the Zoological Institute of the Russian Academy of Sciences (St. Petersburg, Russia). Macrosaldula graziae sp. nov., from South Uzbekistan and Tajikistan, is described. Among the Central Asian species of the genus, it is close to M. tadzhika (Kiritshenko, 1912) by the presence of long erect setae on the body dorsum, but the latter species differs in the smaller body size, the presence of light spots on the corium, and in the structure of the male genitalia. In extremely dark specimens of M. jakowleffi (Reuter, 1891), the hemelytra are opaque, with short erect setae. Siberian M. rivularia (J. Sahlberg, 1878), M. simulans Cobben, 1985 and the Far Eastern M. koreana (Kiritshenko, 1912) and M. violacea Cobben, 1985 are distinguished from the new species by the short pubescence on the dorsum. We provide new distributional data for M. clavalis Cobben, 1985 (Georgia), M. jakowleffi (Reuter, 1891) (China: Xinjiang: Altai Mts.—first record), M. miyamotoi Cobben, 1985 (Japan: Honshu), M. nivalis (Lindberg, 1935) (Afghanistan—first record, Kyrgyzstan, Tajikistan), M. scotica (Curtis, 1835) (Georgia: Adzharia; Russia: Murmansk District), and M. tadzhika (Afghanistan—first record, Tajikistan, Uzbekistan). The record of M. scotica from Uzbekistan is disconsidered, and the two specimens are referred to M. graziae sp. nov.